2022
DOI: 10.34190/ejel.20.4.2201
|View full text |Cite
|
Sign up to set email alerts
|

From face-to-face to Distance: Towards Flexibility in five Dimensions of Blended Learning: Lessons Learnt from the Covid-19 Pandemic

Abstract: In the rapid switch from contact to distance learning in response to the 2020 Covid-19 pandemic lecturers had to adapt their teaching in relation to five distinct areas – place, time, class size, technology, and pedagogy. This autoethnography reflects on the implications of each of those dimensions, as well as the extent to which lecturers worked either at the extremes or the dimension, or in a way to incorporate elements of both extremes. From the narratives of how lecturers cope I derive a matrix for the sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 29 publications
2
9
0
3
Order By: Relevance
“…The findings of this study suggested the flexibility of synchronous and asynchronous blended learning without compromising learning quality (Müller & Mildenberger, 2021), thus supporting the previous research (Cronje, 2022;Howell, 2022;Moorhouse & Wong, 2022). The implementation of synchronous and asynchronous blended learning met the four aspects of flexible blended learning as proposed by Cronje (2022) and Veletsianos and Houlden (2019) including place, time, service, technology and pedagogy. Regarding the place, synchronous and asynchronous blended learning facilitated students to join courses and participate in the MBKM program at the same time.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The findings of this study suggested the flexibility of synchronous and asynchronous blended learning without compromising learning quality (Müller & Mildenberger, 2021), thus supporting the previous research (Cronje, 2022;Howell, 2022;Moorhouse & Wong, 2022). The implementation of synchronous and asynchronous blended learning met the four aspects of flexible blended learning as proposed by Cronje (2022) and Veletsianos and Houlden (2019) including place, time, service, technology and pedagogy. Regarding the place, synchronous and asynchronous blended learning facilitated students to join courses and participate in the MBKM program at the same time.…”
Section: Discussionsupporting
confidence: 85%
“…4. The generated themes were classified under the conceptual framework of flexibility in blended learning, including place, time, service, technology and pedagogy (Cronje, 2022;Veletsianos & Houlden, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the shift to virtuality was a necessary response to the global setting, it brought about significant challenges and insights into the student experience, such as motivational issues, feelings of isolation, and adaptation to new technologies (Caprara and Caprara, 2022). Now, as they return to face-to-face modalities, institutions need to consider integrating lessons learned during remote education and address students' concerns and expectations, who have undergone a significant transformation in their learning approach (Cronje, 2022;Singh et al, 2022). Returning to physical classrooms does not merely mean reverting to old practices but adapting to a new educational normal influenced by the virtual experience (Tilak and Kumar, 2022;Bridges et al, 2023).…”
Section: Introductionmentioning
confidence: 99%